Trypanosoma brucei Metacaspase 4 Is a Pseudopeptidase and a Virulence Factor - Proto, William R. (American Society for Biochemistry and Molecular Biology, 2011)
Metacaspases are caspase family cysteine peptidases found in plants, fungi, and protozoa but not mammals. Trypanosoma brucei is unusual in having five metacaspases (MCA1–MCA5), of which MCA1 and MCA4 have active site substitutions, making them possible non-enzymatic homologues. Here we demonstrate that recombinant MCA4 lacks detectable peptidase activity despite maintaining a functional peptidase structure. MCA4 is expressed primarily in the bloodstream form of the parasite and associates with the flagellar membrane via dual myristoylation/palmitoylation. Loss of function phenotyping revealed critical roles for MCA4; rapid depletion by RNAi caused lethal disruption to the parasite's cell cycle, yet the generation of MCA4 null mutant parasites (Δmca4) was possible. Δmca4 had normal growth in axenic culture but markedly reduced virulence in mice. Further analysis revealed that MCA4 is released from the parasite and is specifically processed by MCA3, the only metacaspase that is both palmitoylated and enzymatically active. Accordingly, we have identified that the multiple metacaspases in T. brucei form a membrane-associated proteolytic cascade to generate a pseudopeptidase virulence factor.